Grade 10-12 learners' attitude towards mathematics and how the attitudes affect performance - Ndlovu, Vusumuzi (My University, 2017)
The role of learner attitude in the learning of mathematics has given rise to numerous research on the subject with most research providing several empirical evidence on the relationship between learner attitude towards mathematics and their performance in the subject. The present study was designed so as to explore the influence of some attitude dimensions that learners have towards mathematics and relate these attitudes measures to the performance of the learners and also find out if some of these attitudes factors are gender related. The study was carried out in one of the Soweto schools; a total of 231 learners from Grade 10 – 12 were involved in the completion of a questionnaire, followed by interviews with 10 learners across the three grades. Therefore, a mixed method approach (quantitative and qualitative methods of collecting data) was used. The instrument used for the questionnaire was tested for reliability using Cronbach’s alpha and the correlations established between the various attitudes measures and the June examination scores for the learners. This revealed some mixed results ranging from a general weak correlation between attitude and the performance of the learners in lower grades to generally high positive correlation in the higher grades, consistent with existing literature on attitude and performance. It was also found that gender played a major role in learner attitudes which was not very consistent with most existing literature on gender and attitude towards the learning of mathematics. The study also unveiled some external factors that could affect learners in the learning of mathematics including the teacher, pressure from other learners and the community in general, as well as school policy on the choice of mathematics and mathematical literacy.
A research report submitted to the school of Education, University of Witwatersrand, in partial fulfilment for the requirements for the degree of Master of Education by coursework and research report. Johannesburg, March 2017
Keywords: Mathematics--Study and teaching (Secondary)--South Africa; Mathematics--Study and teaching--Social aspects--South Africa